ACE2 expression is related to the interferon response in airway epithelial cells but is that functional for SARS-CoV-2 entry?. (April 2021) - Scagnolari, Carolina; Bitossi, Camilla; Viscido, Agnese; Frasca, Federica; Oliveto, Giuseppe; Scordio, Mirko; Petrarca, Laura; Mancino, Enrica; Nenna, Raffaella; Riva, Elisabetta; De Vito, Corrado; Midulla, Fabio; et al.
Graphical abstract: Highlights: Combined expression of ACE2 isoforms was higher in virus-infected children than in adults. In patients ACE2 expression level was consistently associated with that of ISG15. The furin level was not correlated with patient's age nor with ISG15. Cell lines' stimulation by type I/III Interferons induced only the truncated ACE2 isoform. Abstract: In vitro interferon (IFN)α treatment of primary human upper airway basal cells has been shown to drive ACE2 expression, the receptor of SARS-CoV-2. The protease furin is also involved in mediating SARS‐CoV‐2 and other viral infections, although its association with early IFN response has not been evaluated yet. In order to assess the in vivo relationship between ACE2 and furin expression and the IFN response in nasopharyngeal cells, we first examined ACE2 and furin levels and their correlation with the well-known marker of IFNs' activation, ISG15, in children (n = 59) and adults (n = 48), during respiratory diseases not caused by SARS-CoV-2. A strong positive correlation was found between ACE2 expression, but not of furin, and ISG15 in all patients analyzed. In addition, type I and III IFN stimulation experiments were performed to examine the IFN-mediated activation of ACE2 isoforms (full-length and truncated) and furin in epithelial cell lines. Following all the IFNs treatments, only the truncated ACE2 levels, were upregulated significantly in the A549 and Calu3 cells, in particular by type I IFNs. If confirmed in vivo following IFNs' activation, the induction of the truncated ACE2 isoform only would not enhance the risk of SARS‐CoV‐2 infection in the respiratory tract.